Accelerated CSharp 2008 - Nash, Trey (Apress, 2012)
Programming is exhilarating. It is a breathtaking venture through problems of the mind accented by beautiful vistas as solutions are discovered. Throughout the process, a programmer’s view of the problems he solves and the solutions to these problems is formed through the lens of the language that he uses and thinks in. So, it is important for a programmer to become intimately familiar with that language. The problems that developers work on are as varied as the developers themselves. They range from medical applications to insurance software, from multimedia applications to data mining tools. The evolution of C# really is about the evolution of the problems that developers face. As the problems become ever more complex, the language becomes simpler and more powerful to deal with the complexity.